Ratcheting assessment of 304 steel samples by means of two kinematic hardening rules coupled with isotropic hardening descriptions. (December 2018) - Karvan, P.; Varvani-Farahani, A.
Highlights: Ratcheting strain of 304 steel samples was predicted by the O–W and A–V kinematic models. Ratcheting over the first 100 cycles was modified through adherence of isotropic description. Through isotropic-kinematic frameworks, predicted ratcheting agreed well with experimental data. Hysteresis loops showed changes in width over loading cycles as isotropic was included. Modulus of plasticity and ratcheting rate were evaluated through the A–V and O–W frameworks. Abstract: Ratcheting response of 304 stainless steel samples was predicted by means of the Ohno–Wang (O–W) and the Ahmadzadeh–Varvani (A–V) kinematic hardening rules in the presence of isotropic hardening rules of Lee and Zavrel (Iso-LZ), Chaboche (Iso-C), and Kang (Iso-K). Expansion and translation of yield surfaces were studied when isotropic hardening rules were adhered to kinematic hardening rules. The backstress increments in the O–W model were developed based on the Armstrong–Fredrick (A–F) model and activated through the power law description of the O–W model. The dynamic recovery term in the A–V model possessed an internal variable to control the variation of backstress, yield surface translation, and plastic strain accumulation over loading process. The inclusion of isotropic hardening models involved an exponential function to achieve a saturated value of yield stress while controlling the rate of evolution through an exponent, β, and parameter Q representing saturated value of isotropic internal variable R . The influence of isotropic models coupled with the kinematic hardening rules of O–W and A–V on ratcheting response of steel samples was discussed. Graphicalabstract : Image, graphical abstract